If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + (x + 5) + (x + -3) = 35 Reorder the terms: X + (5 + x) + (x + -3) = 35 Remove parenthesis around (5 + x) X + 5 + x + (x + -3) = 35 Reorder the terms: X + 5 + x + (-3 + x) = 35 Remove parenthesis around (-3 + x) X + 5 + x + -3 + x = 35 Reorder the terms: 5 + -3 + X + x + x = 35 Combine like terms: 5 + -3 = 2 2 + X + x + x = 35 Combine like terms: x + x = 2x 2 + X + 2x = 35 Solving 2 + X + 2x = 35 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + X + -2 + 2x = 35 + -2 Reorder the terms: 2 + -2 + X + 2x = 35 + -2 Combine like terms: 2 + -2 = 0 0 + X + 2x = 35 + -2 X + 2x = 35 + -2 Combine like terms: 35 + -2 = 33 X + 2x = 33 Add '-2x' to each side of the equation. X + 2x + -2x = 33 + -2x Combine like terms: 2x + -2x = 0 X + 0 = 33 + -2x X = 33 + -2x Simplifying X = 33 + -2x
| x(x+5)(x-1)=0 | | 6-6x=5x-8x+15 | | x^2+y^2+z=1 | | 5(6y-4)+19=3(4y+4)+7 | | 3(2y-4)+18=4(3y+1)+1 | | x^2+y^2-z=1 | | 7x-3=2x-5 | | 14x-20-13x=-14 | | 6x+7x-76=95-6x | | 105=(p^2-p) | | -18x-13=15x-4 | | x^2-37x-120=0 | | s=(p^2-p) | | 8x+4=4x+6 | | 9(x+4)+2=-9(x-8)-6 | | 7x+3=6(x+8)-8 | | 8c^2-24c+16=0 | | x+5x=-48 | | (x+3)(x+3)=-4x-15 | | p^2-64=0 | | 5.2x=29.64 | | -4x+1=21 | | p^2+1p=0 | | 2z(3z-1)=9z-3 | | p(p-16)=-48 | | x^2=1x+90 | | 2x-0.1=6.6x-37.82 | | -6y+4(6y-6)=-5+7(1-y) | | 1(x-7)-6=-4(x+8) | | 2(4x+1)=4x-12 | | 5x+2=3x+1 | | 11(x-6)-6=31x-232 |